2019
DOI: 10.5578/turkjsurg.4223
|View full text |Cite
|
Sign up to set email alerts
|

The predictive power of SAPS-3 and SOFA scores and their relations with patient outcomes in the Surgical Intensive Care Unit

Abstract: Objective: Individual risk of surgical patients is more often underestimated and there is not an absolute criterion demonstrating which patient deserves intensive care. Since a nominative assessment of these patients to quantify the intensity of critical illness is not appropriate, prognostic scores are used to assess the mortality rate and prognosis for critical patients including surgical ones. This study aimed to test the calibration power of SAPS-3 score and SOFA score of surgical patients undergoing gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
4
4
0
Order By: Relevance
“…Similar results are published by Basile-Filho et al, who revealed an AUCROC of 0.79 by using the SOFA score for the prediction of mortality within 847 surgical ICU patients [32]. Contrarily, Mungan et al showed a lower predictive validity of 0.63 of the SOFA score in surgical ICU patients [33]. Although authors of these studies described their population as "surgical patients," it must be highlighted that their calculations comprised all kinds of surgical patients, independently of their risk for infection, including those without suspicion of infection.…”
Section: Discussionsupporting
confidence: 85%
“…Similar results are published by Basile-Filho et al, who revealed an AUCROC of 0.79 by using the SOFA score for the prediction of mortality within 847 surgical ICU patients [32]. Contrarily, Mungan et al showed a lower predictive validity of 0.63 of the SOFA score in surgical ICU patients [33]. Although authors of these studies described their population as "surgical patients," it must be highlighted that their calculations comprised all kinds of surgical patients, independently of their risk for infection, including those without suspicion of infection.…”
Section: Discussionsupporting
confidence: 85%
“…Similar results are published by Basile-Filho et al, who revealed an AUCROC of 0.79 by using the SOFA score for the prediction of mortality within 847 surgical ICU patients [33]. Contrarily, Mungan et al showed a lower predictive validity of 0.63 of the SOFA score in surgical ICU patients [34]. Although authors of these studies described their population as "surgical patients", it must be highlighted that their calculations comprised all kinds of surgical patients, independently of their risk for infection, including those without suspicion of infection.…”
Section: Discussionsupporting
confidence: 85%
“…Similar results are published by Basile-Filho et al, who revealed an AUCROC of 0.79 by using the SOFA score for the prediction of mortality within 847 surgical ICU patients [29]. Contrarily, Mungan et al showed a lower predictive validity of 0.63 of the SOFA score in surgical ICU patients [30]. Although authors of these studies described their population as "surgical patients", it must be highlighted that their calculations comprised all kinds of surgical patients, independently of their risk for infection, including those without suspicion of infection.…”
Section: Discussionsupporting
confidence: 85%